A comparative study of biochemical indicators of iron concentration in two groups of pregnant women, with and without pre-natal care - Szarfarc, Sophia Cornbluth; Siqueira, Arnaldo Augusto Franco de; Martins, Ignez Salas; Tanaka, Ana Cristina D'Andretta (Revista de Saúde Pública, 1982)
The influence of the amount of pre-natal care on the prevalence of iron-deficiency among women, 36 weeks or more pregnant, was assessed. The sample population was divided into three groups: the Standard Group (GP) - with adequate assistance of the pre-natal care services from the first trimester of pregnancy onwards; those who received pre-natal assistance, but of varying adequacy and begun at different gestational ages (CPN); and those who received no pre-natal assistance at all (SPN). The results obtained from hemoglobin analysis showed that prevalence and severity of anemia increases significantly from the GP to the SPN. The analysis of the mean corpuscular hemoglobin concentration, serum iron and transferrin saturation showed no statistically significant differences between groups CPN and SPN; the GP showed better results when compared to the other two. Attention is called to the necessity of pre-natal care and the standardization of its quality with a view to diminishing the prevalence of iron-deficiency among pregnant women.